RESPONS PESERTA DIDIK TERHADAP PEMBELAJARAN MENULIS PUISI MENGGUNAKAN MODEL PROJECT BASED LEARNING BERBANTUAN CANVA DI KELAS VIII - Savitri, Destian; Wikanengsih; Salamah Azzahra, Iis Siti (IKIP Siliwangi, 2025)
Learning with the Project Based Learning model is an interactive learning that can create a pleasant learning atmosphere. The Canva is a digital medium that can be combined with the Project Based Learning learning model to help students create poetry writing by leveraging advanced features in the Canva such as adding elements, images, and fonts, as well as available online, paid, and free ready-to-use frame examples. The aim of this study is to find out how the students respond to the Learning to the poetic writing material and the obstacles encountered by the students during the process of learning to write poetry with the project based learning model assisted by Canva. It was studied using Qualitative Descriptive research methods. The sample used was all the students of the eighth grade A SMC Advent Cimindi of 25 people. The data was taken using an elevator containing 10 statements consisting of 5 positive statements and 5 negative statements as well as 1 question about the impediments of the students during the learning process. The results of the study indicated that the respondents obtained an average percentage of 60% with the category Good enough. As for the constraints experienced by the students are lack of understanding of the Canva and Lack of stability of the Internet to access the Canva.